Virulence factors in Escherichia coli strains isolated from urinary tract infection and pyometra cases and from feces of healthy dogs - Siqueira, Amanda K. [UNESP]; Ribeiro, Márcio Garcia [UNESP]; Leite, Domingos da S.; Tiba, Monique R.; Moura, Claudia de; Lopes, Maria Denise [UNESP]; Prestes, Nereu Carlos [UNESP]; Salerno, Tatiana [UNESP]; Silva, Aristeu V. da (Elsevier B.V., 2009)
The aim of this study was to compare the prevalence of virulence genes in 158 Escherichia coli strains isolated from 51 clinical cases of UTIs, 52 of pyometra and from 55 fecal samples from healthy dogs by PCR. papC was found in 12 (23.5%) strains isolated from UTIs, 19 (36.5%) from pyometra and 10 (18.2%) from feces. papGII was observed in 3 (5.8%) strains from pyometra, and papGIII in 10 (19.6%) from UTIs, 15 (28.8%) from pyometra and 9 (16.4%) from feces. sfaS was detected in 22 (43.1%) strains from UTIs, 24 (46.1%) from pyometra and 19 (34.5%) from feces. hlyA was observed in 17 (33.3%) strains from UTIs, 18 (34.6%) from pyometra and 7 (12.7%) from feces, while cnf-1 was detected in 11 (21.6%) from UTIs, 21 (40.4%) from pyometra and 9 (16.4%) from feces. iucD was observed in 12 (23.5%) strains from UTIs, 9 (17.3%) from pyometra and 1 (1.8%) from feces. usp was found 17 (33.3%) isolates from UTIs and 36 (69.9%) from pyometra. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: Escherichia coli; Dog; Virulence factors; Urinary tract infection; Pyometra